The Impact of Specific Physical Training on FGF-2 and VEGF-A Expression in Patients Post-Coronary Artery Bypass Surgery. - Monjezi, Maryam; Barari, Alireza; Abdi, Ahmad (Journal of Basic Research in Medical Sciences, 2024)
Introduction: Coronary artery bypass surgery (CABG) is a common procedure for patients with coronary artery disease. This study aimed to investigate the effect of selected physical exercises on the expression of FGF-2 and VEGF-A in patients post-CABG. Material & Methods: In this semi-experimental study, 20 male patients from Afshar Hospital (Yazd City) who had undergone CABG were selected and randomly divided into two groups: a combined training group and a control group. The combined training group performed an 8-week program consisting of endurance training (15-20 minutes at 50-60% of HRmax) and resistance training (10-20 minutes, including three upper limb and two lower limb movements, each with three sets of 10 repetitions at 3060% of 1RM), conducted three times per week. Gene expression of Fibroblast Growth Factor 2 (FGF-2) and Vascular Endothelial Growth Factor A (VEGF-A) was measured using Real-Time PCR. Data were analyzed using paired t-tests and one-way ANOVA with a significance level set at P<0.05. Results: An increase in the expression of VEGF and FGF-2 genes was observed in the combined training group post-test compared to pre-test (p=0.019). Additionally, there was a significant difference in VEGF gene expression between the control and training groups (p=0.016). Significant differences were also found in FGF-2 expression between the combined exercise group and both the healthy control and patient control groups (p=0.001 for both). Conclusion: The results suggest that combined exercises may enhance physiological adaptations and improve the functional capacity of the heart and vessels in CABG patients by increasing growth factor expression.